Palynological zonation of the Lajas Formation (Middle Jurassic) of the Neuquén Basin, Argentina (Ameghiniana, 2014)
A new palynological zonation for the Middle Jurassic of the southern part of the Neuquén Basin is presented. Two zones and eight subzones based on sporomorphs and associated microplankton of late Aalenian to early Callovian age are defined. These zones are correlated with previous palynological zonations in the Neuquén Basin. The macropaleontologic (mainly ammonites) and micropaleontologic content (relative frequencies of taxa and suprageneric groups) of each depositional sequence previously identified in the study area by other workers are given.